2021
DOI: 10.3390/ijerph181910397
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Sleep Problems among Russian Adolescents: A Field School-Based Study

Abstract: This study aims to establish a link between disturbances in the night sleep habitus, quality of sleep, and daytime sleepiness in adolescents with Internet addiction and different types of content consumed. Methods: This is a cross-sectional observational study of a school sample in three large cities in Central Siberia. 4615 schoolchildren of 12–18 years old were examined. The Russian-language versions of the Chen Internet Addiction Scale, the Game Addiction Scale for Adolescents, and the Social Media Disorder… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
2
16
0
1
Order By: Relevance
“…To date, although a few studies have examined internet use and smartphone use in adolescents, middle and high school students (17)(18)(19)(20)(21)(22), few studies examined the smartphone use pattern and PMPU among university students in China during the COVID-19 pandemic. Furthermore, no studies have examined the association between PMPU and life satisfaction using standard structured instruments.…”
Section: Introductionmentioning
confidence: 99%
“…To date, although a few studies have examined internet use and smartphone use in adolescents, middle and high school students (17)(18)(19)(20)(21)(22), few studies examined the smartphone use pattern and PMPU among university students in China during the COVID-19 pandemic. Furthermore, no studies have examined the association between PMPU and life satisfaction using standard structured instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that depression, anxiety and impulsive are common comorbid diseases of PIU ( 53 , 54 ). Simultaneously, previous studies have reported that excessive time spent online can reduce the required night sleep with internet addiction patients, furthermore leading to sleep disorders ( 55 , 56 ). Our previous research also found that PIU individuals had higher SDS, SAS and BIS-11 scores, and more poor sleep quality compared with individuals without PIU ( 33 ).…”
Section: Discussionmentioning
confidence: 93%
“…Our results draw attention because it suggests a modi cation of teenagers on their choice and time in an electronic devices. TV could be to leave their bad place and probably would have to create several interventions to ght avoid all day time spent on cell phone (35). Independently of all other important factors such as mental risk factors, dietary and cell phone seems to be the main predictors of insu cient and inadequate sleep time.…”
Section: Discussionmentioning
confidence: 99%